Islamic law - Ali Mohamed, Ashgar Ali (Malaysian Current Law Journal, 2014)
Islamic law or ‘Syariah’ is a system of law and ethics based on the divine will of Allah (SWT) that was revealed to the Prophet Muhammad (SAW) over a period of 23 years beginning 610 AD. The Syariah is thus divinely inspired, intimately linked to religious tenets, encompassing in broad principles the whole sphere of human life, and provides the basic moral and legal framework on a wide range of transactions. As noted earlier, during the era of European colonial powers in the Malay Peninsula, Islamic law was implemented gradually. However, due to the colonisation of the Straits Settlements and the establishment of British administrations in the Malay States, the relevancy of Islamic law were gradually limited to certain personal matters affecting the Muslims. Hence, this chapter discusses the status and position of Islamic law before and during the British administrations of the Malay Peninsula. Apart from the above, the status and position of Islamic law in the Federal Constitution, the supreme law of the Federation, is also covered in this chapter. Further, the chapter also covered the Syariah court’s jurisdiction. The recognition of the Syariah courts was largely due to art. 121(1A) of the Federal Constitution which excludes the jurisdiction of the civil courts in respect of any matter that comes within thejurisdiction of the Syariah courts. It must be added that the Syariah court’s jurisdiction is only over persons professing the religion of Islam and further, only in respect of any of the matters enumerated in list II of the State List of the Ninth Schedule to the Federal Constitution.